Evaluation of cold mix patching materials along Jalan Persiaran Mokhtar Dahari, Selangor - Ekarizan, Shaffie; Ahmad Kamil, Arshad; Anizahyati, Alisibramulisi; Mohd Amin, Shafii; Putra Jaya, Ramadhansyah; Khairil Azman, Masri (Springer, 2021)
The increasing of road accidents and the economic loss due to maintenance operation is becoming an important issue in Malaysia asphalt industry. Potholes are the most common distress occurred in asphalt pavement which require immediate attention to minimise further pavement damage and reduce the opportunity for potential accidents. Hence, a study was conducted to evaluate the performance of six commercially available cold mix asphalt products in Malaysia. Six kinds of patching materials that is nominated as a company sample A, B, C, D, E and F currently used in practice were tested in the laboratory. The laboratory tests included the sieve analysis, density analysis, bitumen content, volumetric properties and moisture susceptibility test. The result of the laboratory tests indicates that the gradation for all the samples are close to the gradation requirements for the AC14 mix as per JKR Malaysia’s specification. However, none of the samples fully complied with the gradation envelope. For density, all the samples are lower than the requirements for the AC14 mix and none of the samples fully complied with the compaction requirements due to the compaction method using the plate compactor. Meanwhile, for volumetric properties results, stability values of the various cold mix samples met the standard specification. Based on the ranking performance criteria of six different cold mix patching materials, Sample B and Sample D obtained the highest score of compliance with the requirements of the specification.